1996
DOI: 10.1136/jnnp.61.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in low grade (WHO grade II) gliomas of the cerebral hemispheres: the role of surgery.

Abstract: Results-The overall survival probability at five years was 971%, at eight years 76-1%, and at 10 years 62-7% (median survival time 144 months). The impact on survival of the following variables was analysed: age (<20, 21-40, and >40 years), Karnofsky score (80-100, 70, < 70), histology, tumour extension (Ti <3 cm, T2 3-5 cm, T3 > 5 cm maximum diameter), extent of surgical resection (SI radical, S2 subtotal <10% residual tumour, S3 partial-10%/o-50% residual tumour), and radiotherapy (either performed or not). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(57 citation statements)
references
References 42 publications
2
55
0
Order By: Relevance
“…Any study that reported better survival rates had included children, oligodendroglioma, WHO Grade 1 astrocytoma, predominantly lobar tumors, or had much shorter follow-up periods. [1][2][3][7][8][9]22 The well known 5-year experience is now extended to more than 10 years; Ten-year overall survival and 10-year progression-free survival were 37% and 21%, and 15-year survival and 15-year progression-free survival rates were 26% and 14%, respectively. Laws et al, who have presented long-term results of a large and heterogeneously composed study group treated before the advent of CT (by various degrees of tumor resection and external-beam radiation), reported 10-and 15-year survival rates of 21% and 18%, respectively.…”
Section: Outcomementioning
confidence: 95%
“…Any study that reported better survival rates had included children, oligodendroglioma, WHO Grade 1 astrocytoma, predominantly lobar tumors, or had much shorter follow-up periods. [1][2][3][7][8][9]22 The well known 5-year experience is now extended to more than 10 years; Ten-year overall survival and 10-year progression-free survival were 37% and 21%, and 15-year survival and 15-year progression-free survival rates were 26% and 14%, respectively. Laws et al, who have presented long-term results of a large and heterogeneously composed study group treated before the advent of CT (by various degrees of tumor resection and external-beam radiation), reported 10-and 15-year survival rates of 21% and 18%, respectively.…”
Section: Outcomementioning
confidence: 95%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Current primary treatment options include surgical resection and/or radiotherapy, although definitive evidence for an optimal treatment remains elusive. Advances in molecular epidemiology indicate that certain histologic subtypes of low-grade gliomas, such as oligodendrogliomas, may have varied response to chemother- apeutic agents based on chromosomal changes, including loss of chromosome 1p and/or 19q, and, hence, may have improved survival with use of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many projects [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] that have examined the association between both the use and the extent of surgical resection with outcomes for neurosurgical patients who are diagnosed with low-grade gliomas, 3 the relation remains unclear. In addition, although previous studies have examined the role of intraoperative magnetic resonance imaging (MRI) in tumor volume measurement, 18,20 the reports that exist generally are relatively small in size, present estimates that were not adjusted for age and/or histology, vary by study patient composition, or present study results in nonstandard statistical format.…”
mentioning
confidence: 99%
“…[1][2][3][4] Several studies have attempted to identify prognostic factors in LGG. 1,[5][6][7][8][9][10][11][12] Prognostic factors have various applications that could be of particular value in the heterogeneous population of LGG. This includes guidance for stratification in phase III trials and ultimately for treatment in individual patients.…”
Section: Ow-grade Gliomas (mentioning
confidence: 99%